Current status of asian elephant population Elephas maximus in Pumat National Park Region, Nghe An Province - Nghia, Nguyen Xuan; Dat, Nguyen Tien; Dang, Nguyen Xuan; Cuong, Tran Xuan; Tuan, Vo Cong Anh (Academia Journal of Biology, 2020)
Asian elephants are under high threats of extinction in Vietnam and worldwide. Population assessment of Asian elephants in Pumat National Park (NP) region, carried out in 2018−2019, showed that the wild Asian elephants population this region consisted of 3 groups with a total of 13−14 individuals. In Tuong Duong District, a group of 4-5 individuals lived in an area near Canh Ta stream (Tam Dinh commune, Vietnam) and Nam Xi stream (Muong Long commune, Laos), across the border between Vietnam and Laos. The group in Con Cuong district, with only one adult female, lived in forest compartments 780, 781,789 and 786 of Con Cuong Forestry Company, within the buffer zone of Pumat NP. The group in Anh Son district consisted of 8 individuals (5 adult females, 1 adult male, 1 sub-adult male and an juvenile born in 2016). They live in Cao Veu sector of Pumat NP core zone and buffer zone areas consisting of protected forests, rubber plantation forests and agricultural lands of households in Phuc Son Commune (Anh Son District) and Thanh Duc Commune (Thanh Chuong District).Wild Asian elephants in Pumat NP region are facing dangers of extinction due to their small number as well as direct and indirect threats from human. The elephant group in Anh Son district, with the largest number of individuals consisting of breeding males, breeding females and a calf, is the most important for the maintainance and future development of elephant population within Puman NP. However, they are facing a number of  serious threats such as: un-controlled wildlife hunting and trade; rapid decrease and degradation of natural forest outside of Pumat National Park; and increasingly serious human-elephant conflicts.